2012
DOI: 10.1098/rstb.2011.0187
|View full text |Cite
|
Sign up to set email alerts
|

From actors to agents in socio-ecological systems models

Abstract: The ecosystem service concept has emphasized the role of people within socio-ecological systems (SESs). In this paper, we review and discuss alternative ways of representing people, their behaviour and decision-making processes in SES models using an agent-based modelling (ABM) approach. We also explore how ABM can be empirically grounded using information from social survey. The capacity for ABM to be generalized beyond case studies represents a crucial next step in modelling SESs, although this comes with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
124
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 55 publications
0
124
0
1
Order By: Relevance
“…Through model development and integration, knowledge is synthesized, formalized in mathematics or computer code, communicated and discussed among others, and gaps in knowledge and data are identified that create an iterative modelling process (Rounsevell et al 2012). Finally, coupled models will be most useful if we 5 can use them to test possible interventions in the Earth system that might help avoid the worst possible outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Through model development and integration, knowledge is synthesized, formalized in mathematics or computer code, communicated and discussed among others, and gaps in knowledge and data are identified that create an iterative modelling process (Rounsevell et al 2012). Finally, coupled models will be most useful if we 5 can use them to test possible interventions in the Earth system that might help avoid the worst possible outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The meeting presupposed the need to consider the ecological impact of anthropogenic environmental changes as a major rationale for the need to make ecological predictions. Clearly, human activity often plays an important role in structuring ecosystems and is frequently a driver of change within ecosystems [40,41]. The exclusion of humans from ecological models seems artificial, and although there are some good examples in which individual-or agent-based models of human populations (agent-based models (ABMs) in the social sciences being essentially similar to individual-based models in ecology) and biosphere models have been successfully coupled to produce predictions about the fate of the ecosystem and consequences to the human population [42], these are unusual.…”
mentioning
confidence: 99%
“…The exclusion of humans from ecological models seems artificial, and although there are some good examples in which individual-or agent-based models of human populations (agent-based models (ABMs) in the social sciences being essentially similar to individual-based models in ecology) and biosphere models have been successfully coupled to produce predictions about the fate of the ecosystem and consequences to the human population [42], these are unusual. Agent-based modelling is regarded as an appropriate tool for understanding human decisionmaking and is often used in models of humanenvironment interactions [40,41]. Rounsevell [40] identifies that many of the issues that concern the ecological community about individual-based models (IBMs) are also of concern to social scientists using ABMs of human systems.…”
mentioning
confidence: 99%
See 2 more Smart Citations